(untitled) (Journal of Computational Mathematics, 2021)
Least squares solution of F=PG with respect to positive semidefinite symmetric P is considered, a new necessary and sufficient condition for solvability is given, and the expression of solution is derived in the some special cases. Based on the expression, the least squares solution of an inverse eigenvalue problem for positive semidefinite symmetric matrices is also given.